Design considerations of biaxially tensile-strained germanium-on-silicon lasers. (28th April 2016) - Li, Xiyue; Li, Zhiqiang; Li, Simon; Chrostowski, Lukas; Xia, Guangrui (Maggie)
Abstract: Physical models of Ge energy band structure and material loss were implemented in LASTIP TM, a 2D simulation tool for edge emitting laser diodes. This model is able to match available experimental data. Important design parameters of a Fabry–Perot Ge laser, such as the cavity length, thickness, width, polycrystalline Si cladding layer thickness were studied and optimized. The laser structure optimizations alone were shown to reduce I th by 22-fold and increase η d and η i by 11 and 6 times. The simulations also showed that improving the defect limited carrier lifetime is critical for achieving an efficient and low-threshold Ge laser. With the optimized structure design (300 μ m for the cavity length, 0.4 μ m for the cavity width, 0.3 μ m for the cavity thickness, and 0.6 μ m for the polycrystalline Si cladding layer thickness) and a defect limited carrier lifetime of 100 ns, a wall-plug efficiency of 14.6% at 1 mW output is predicted, where J th of 2.8 kA cm −2, I th of 3.3 mA, I 1mW of 9 mA, and η d of 23.6% can be achieved. These are tremendous improvements from the available experimental values at 280 kA cm −2, 756 mA, 837 mA and 1.9%, respectively.